Abundance and Species Richness of Leafhoppers and Planthoppers (Hemiptera: Cicadellidae and Delphacidae) in Brazilian Maize Crops - De Oliveira, Charles Martins (2013)
Fil: De Oliveira, Charles Martins. Embrapa Cerrados. Planaltina. Brasília/DF; Brazil